Wellness and Herbal Tourism Based on Local Wisdom as an Alternative to ‘New Normal’ Tourism - Widarini, Paramita Sari Indah; Wijaya, Mahendra; I N, Albert Muhammad (Jurnal Komunikasi, 2022)
The government initiated a wellness and herbal tourism program, in collaboration with the Indonesian Ministry of Tourism and Creative Economy with the Ministry of Health. This tourism cluster is prioritized because it has high impact in improving health, cultural and economic field. This type of tourism is considered would provide fresh air in the New normal situations that require people to remain side by side with the Covid-19 pandemic situation. The author examines concretely the marketing communication strategy of tourism stakeholders in developing the program to see how the establishment of wellness and herbal tourism based on local wisdom as an alternative in tourism industry, especially in the New normal era. The author uses a marketing communication strategy with the SOSTAC + 3Ms model of marketing communication analysis, which was popularized by PR. Smith. This theory is considered could describe the integrated marketing communication science in the tourism industry. This research was conducted using a qualitative descriptive method, with an emphasis on the naturalistic inquiry paradigm. Direct interviews were conducted with competent primary sources who represent their fields. The results of this study describe the tourism stakeholders in Solo have been prepared for the development of the wellness and herbal tourism program, with a focus on the local wisdom of Solo's custom. However, the development and preparation of the wellness and herbal tourism program is deemed not optimal, because internal and external conditions are still hampered tourism business in the midst of the Covid-19 Pandemic.